Tariqah Dimensi Esoteris Dalam Islam (Studi Pemikiran Sayyed Hossein Nasr) - Rahabistara Bistara (Journal of Islamic Civilization, 2020)
This article wants to discuss how tariqah is an esoteric dimension in Islam. This esoteric dimension is an important part of Islam besides the sharia and tauhid dimensions. The esoteric dimension is a subtle part of understanding Islamic teachings. Without this dimension, it is difficult to understand Islam as a whole, because it can be said that this dimension is the heart of Islam itself. Through Sayyed Hossen Nasr's thoughts, this paper wants to describe a reality that has been considered not so important in Islam. This curtain is the tariqah that every human being must pass when he wants to go to God's doors that have been provided by the creator. Without going through this tariqah, as an ordinary human being, it is impossible to get to the doors that have been provided by the creator. By using the library research method, this paper would like to provide an in-depth picture of the aesthetic dimension in Islam through Sayyed Hossein Nasr's point of view.